Relationship between the Condition of the School Environment and the Concentration of Learning in Vocational High School Students - Roza Aktavia; Herman Nirwana (Universitas Negeri Padang, 2019)
This research is motivated by the number of student who have a concentration of learning in the low category. One of the factors that is thought to influence is the condition of the school environment. The purpose of this study is to describe the concentration of students learning, the condition of the school environment, and test a significant positive relationship between the condition of the school environment and the concentration of students learning. The population of the study was 1264 students of Nine Public Vocational School in Padang who were enrolled in the July-December semester of the 2019/2020 academic year and a sample of 330 students was selected by Stratified Random Sampling. The instrument used is the Learning Concentration questionnaire with a reliability of 0.921 and the School Environment Condition questionnaire with a reliabilty of 0.877. Data were analyzed by descriptive techniques and Pearson Product Moment. The research findings are: the concentration of students learning in the medium category, the conditions of the school envinronment in the quite good category, and there is a significant positive relationship between the condition of the school environment and the concentration of learning students.